Child deprivation among Palestinian refugees in Lebanon and Palestinian refugees from Syria living in Lebanon: a cross-sectional analysis of co-occurrence of deprivation indicators. (July 2021) - Jamaluddine, Zeina; Irani, Alexandra; Salti, Nisreen; Abdulrahim, Sawsan; Chaaban, Jad; El-Asmar, Khalil; Ghattas, Hala
Abstract: Background: Palestinian refugees in Lebanon (PRL) and Palestinian refugees from Syria (PRS) living in Lebanon have high poverty rates. As the social, economic, and physical environment in which a child develops is a strong determinant of health and wellbeing, a comprehensive approach that recognises the influence of multidimensional deprivation on child wellbeing is needed. This study investigates overlaps (co-occurrences) in deprivation indicators experienced by Palestinian children compared to those experienced by other vulnerable children living alongside them in Lebanon; children who are Syrian refugees (SYR) and children who are Lebanese nationals (LBN). Methods: This analysis adopted a life-cycle approach using data from the UNICEF 2016 Lebanon Household Survey, and included data on children aged 2–17 years (PRL, n=7106; PRS, n=2768; LBN, n=10555; SYR n=5891). We report on indicators relating to early childhood (24–59 months) and school age (6–17 years), including child survival (nutrition, health, water, sanitation, and overcrowding), child development (education), and child protection (labour, exposure to violence, and early marriage), as well as the co-occurrence of these deprivation indicators. Socio-demographic and geographical correlates of child deprivation were explored using univariate and multivariable logistic regression analysis, a using sampling weights and clustering for children in the same households. Analyses were conducted using Stata 15. Findings: Among children aged 24–59 months, 28·9% (347 of 1202) of PRL and 46·2% (260 of 563) of PRS children were deprived in at least two dimensions, compared with 13·2% (67 of 508) of LBN and 68·5% (915 of 1335) of SYR children. Co-occurring deprivations were highest across the protection and overcrowding dimensions in Palestinian refugee children aged 6–17 years (PRL, 14·2% [769 of 5421]; PRS, 26·7% [531 of 1985]). Across all ages, PRS children were more likely to be deprived in two dimensions than PRL children. However, indicators of health and education deprivation were lower in PRL and PRS children than in SYR children. Geographical disparities in deprivation existed within all four populations, with the highest disparity among those living in North Lebanon and the Bekaa. Higher maternal education (completed intermediate education) was consistently associated with lower odds of having at least two concurrent deprivations among children aged 6–17 years (LBN odds ratio [OR] 0·1, 95% CI 0·1–0·2, p<0·0001; PRL OR 0·3, 95% CI 0·3–0·5, p<0·0001; PRS OR 0·5, 95% CI 0·3–0·7, p=0·0002; SYR OR 0·4, 95% CI 0·2–0·7, p=0·0004). Interpretation: The most common overlaps in deprivation indicators were in housing (overcrowding) and protection (exposure to violence) among PRL and PRS children, highlighting the need to focus simultaneously on housing improvements and protection programmes. Deprivation in health and education were relatively low as PRS children have been included in the well-established UNRWA health and education systems, largely protecting them from poor health and education outcomes. Funding: UNICEF Lebanon. The findings, interpretations, and conclusions do not necessarily reflect the view of UNICEF.